The Garden Realm of Pale Ratiocinations: Toward the Abolition of a Dark Fantastic Theological Imaginary of Human Being - Wood-House, Nathan D. (Political theology, 2024)
Anti-Blackness adumbrates rationality and reaches into phobic realms, what Frantz Fanon called the “paralogical.” Ebony Elizabeth Thomas’s The Dark Fantastic links the dark fantastic imagination and the Dark Other of speculative fiction to their cultural iterations and augments the paralogicality of anti-Blackness by accounting for the narrative roles of hesitation and belief. This paper argues that it is further necessary to assert the narrative significance of nineteenth century Christian, pre-Adamite and/or Serpent Seed theological anthropologies for the production of what one might call a dark fantastic theological imaginary of human being. The paper argues, further, far from being a bygone heresy, the pre-Adamite mythos lives on in the “thin blue line” anthropology of contemporary policing. The paper therefore looks ultimately for abolitionist possibilities to interrupt this imaginary, which it sees in the theological counternarrative of Black being in Matt Ruff’s novel Lovecraft Country and its TV adaptation by Misha Green.